The use of elastic stocking to reduce the risk of varicose vein - Ucke Sugeng Sastrawinata (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To reduce the risk of varicoses in primigravida by wearing elastic stockings with mechanical compression. Method: A prospective study was performed in a randomized single blinded trial with analysis of variance and repeated measures. The study was done at The Obstetrics and Gynecology Department Immanuel Hospital Bandung, with subjects obtained from the Obstetrics outpatient clinic during the period of May 2008 to March 2009. This study consisted of a population of 66 primigravidas randomly allocated in to 2 groups, 34 women in control group and 32 women in study group. Women in the study group were instructed to wear elastic stockings, while the control group was not. Measurements of veins dilatation were carried out using a Color Duplex Ultrasound. Results: The 12 week examination didn’t show any significant change on left femoral veins diameters in both groups. Examination at 34 weeks gestational age showed significant changes on left femoral veins in study group and control group (subsequently 0,83 ± 0,07 cm and 1,02 ± 0,35 cm). It also happened on examination at 2 weeks post-partum. The incidence of reflux was found only in the study group at sapheno-femoral junction in 6 of 34 women. Conclusion: Mechanical compression provide protective effect from the development of varicoses shown by the reduced incidence in developing reflux in blood flow in saphenous-femoral junction, in addition to minimal dilatation of the lower limbs and pelvic veins. [Indones J Obstet Gynecol 2010;34-1:7-11] Keywords: varicoses; pregnancy; endothelial injury; saphenousfemoral junction; reflux; mechanical compression